Extracellular vesicles derived from stressed beta cells mediate monocyte activation and contribute to islet inflammation - Dekkers, Mette C.; Lambooij, Joost M.; Pu, Xudong; Fagundes, Raphael R.; Enciso-Martinez, Agustin; Kats, Kim; Giepmans, Ben N. G.; Guigas, Bruno; Zaldumbide, Arnaud (Frontiers in Immunology, 2024)
Objective: Beta cell destruction in type 1 diabetes (T1D) results from the combined effect of inflammation and recurrent autoimmunity. In recent years, the role played by beta cells in the development of T1D has evolved from passive victims of the immune system to active contributors in their own destruction. We and others have demonstrated that perturbations in the islet microenvironment promote endoplasmic reticulum (ER) stress in beta cells, leading to enhanced immunogenicity. Among the underlying mechanisms, secretion of extracellular vesicles (EVs) by beta cells has been suggested to mediate the crosstalk with the immune cell compartment. Methods: To study the role of cellular stress in the early events of T1D development, we generated a novel cellular model for constitutive ER stress by modulating the expression of HSPA5, which encodes BiP/GRP78, in EndoC-βH1 cells. To investigate the role of EVs in the interaction between beta cells and the immune system, we characterized the EV miRNA cargo and evaluated their effect on innate immune cells. Results: Analysis of the transcriptome showed that HSPA5 knockdown resulted in the upregulation of signaling pathways involved in the unfolded protein response (UPR) and changes the miRNA content of EVs, including reduced levels of miRNAs involved in IL-1β signaling. Treatment of primary human monocytes with EVs from stressed beta cells resulted in increased surface expression of CD11b, HLA-DR, CD40 and CD86 and upregulation of IL-1β and IL-6. Conclusions: These findings indicate that the content of EVs derived from stressed beta cells can be a mediator of islet inflammation.